2021
DOI: 10.1155/2021/9663738
|View full text |Cite
|
Sign up to set email alerts
|

Role of Episamarcandin in Promoting the Apoptosis of Human Colon Cancer HCT116 Cells through the PI3K-Akt Signaling Pathway

Abstract: This study identifies the active ingredients of Ferula sinkiangensis and investigates the role and mechanism of episamarcandin in colon cancer cells. The silica gel column chromatography was utilized to separate the chemical components of Ferula sinkiangensis. Sephadex LH-20 and semipreparative HPLC were adopted for further separation and purification. The compound episamarcandin showed good anticolon cancer activity among the 13 monomeric compounds obtained. Its effects on the apoptosis, cell cycle, and invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…EGFR signalling is also an important marker of colitis-related colorectal carcinogenesis (Ko et al 2019 ; Singh et al 2018 ). PI3K/AKT is a key downstream signalling pathway of EGFR, and abnormal activation of the PI3K/AKT signalling pathway is associated with the development of UC, as well as promoting colon cancer cell proliferation, prolonging cell survival, inhibiting cell apoptosis, and participating in angiogenesis, leading to invasion and metastasis of colon cancer (Jiang et al 2019a , b ; Zhang et al 2021 ). In addition, the PI3K-AKT pathway is closely related to the regulation of the inflammatory response during UC progression.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR signalling is also an important marker of colitis-related colorectal carcinogenesis (Ko et al 2019 ; Singh et al 2018 ). PI3K/AKT is a key downstream signalling pathway of EGFR, and abnormal activation of the PI3K/AKT signalling pathway is associated with the development of UC, as well as promoting colon cancer cell proliferation, prolonging cell survival, inhibiting cell apoptosis, and participating in angiogenesis, leading to invasion and metastasis of colon cancer (Jiang et al 2019a , b ; Zhang et al 2021 ). In addition, the PI3K-AKT pathway is closely related to the regulation of the inflammatory response during UC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Such a discrepancy in IC50 values for inhibition of cell proliferation and induction of apoptosis has been observed for various solid tumor-derived cell lines after exposure to cisplatin or other chemotherapeutic drugs (e.g., oxaliplatin, paclitaxel, and doxorubicin) (for details, see [108][109][110]). apoptosis [111], and ~100 µM cisplatin induced ~30% [112] and ~60% [113] apoptosis in this cell line.…”
mentioning
confidence: 87%
“…Since then, other groups have used different assays and confirmed that very high concentrations of cisplatin are required to engage apoptosis in a significant proportion of cells within HCT116 cultures. For example, 60 µM cisplatin induced ~20% apoptosis [ 111 ], and ~100 µM cisplatin induced ~30% [ 112 ] and ~60% [ 113 ] apoptosis in this cell line. In our own work [ 110 ], we observed higher levels of apoptosis compared to other groups, but, consistent with other groups, we also observed marginal levels of apoptosis at the MTD (~10 µM).…”
Section: Exploiting the Apoptotic Threshold For Managing Solid Tumorsmentioning
confidence: 99%
“…Since then, other groups have used different assays and confirmed that very high concentrations of cisplatin is required to engage apoptosis in a significant proportion of cells within HCT116 cultures. For example, 60 µM cisplatin induced ~20% apoptosis [111], and ~100 µM cisplatin induced ~30% [112] and ~60% [113] apoptosis in this cell line.…”
mentioning
confidence: 99%
“…Since then, other groups have used different assays and confirmed that very high concentrations of cisplatin is required to engage apoptosis in a significant proportion of cells within HCT116 cultures. For example, 60 µM cisplatin induced ~20% apoptosis[111], and ~100 µM cisplatin induced ~30%[112] and ~60%[113] apoptosis in this cell line. In our own work[110], we observed higher levels of apoptosis compared to other groups but, consistent with other groups, we also observed marginal levels of apoptosis at the MTD (~10 µM).…”
mentioning
confidence: 99%